2022
DOI: 10.1177/03000605211063019
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for methicillin-resistantStaphylococcus aureuscolonization and infection in patients with human immunodeficiency virus infection: A systematic review and meta-analysis

Abstract: Objective To investigate the potential factors affecting methicillin-resistant Staphylococcus aureus (MRSA) colonization and infection in patients with human immunodeficiency virus (HIV) infection. Methods A systematic search of publications listed in electronic from inception up to August 2020 was conducted. A random-effects model was used to calculate odds ratio (OR) with 95% confidence interval (CI). Results A total of 31 studies reporting 1410 MRSA events in 17 427 patients with HIV infection were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
(308 reference statements)
1
5
0
Order By: Relevance
“…This study suggested that hospitalisation within the previous year was an independent risk factor for MRSA colonisation. This finding is consistent with other reports about people living with HIV [ 25 , 27 , 28 ] and it may suggest that MRSA was hospital-acquired. Hospitals are known sources of MRSA and nasal colonisation with S. aureus is known to persist in a subset of individuals [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study suggested that hospitalisation within the previous year was an independent risk factor for MRSA colonisation. This finding is consistent with other reports about people living with HIV [ 25 , 27 , 28 ] and it may suggest that MRSA was hospital-acquired. Hospitals are known sources of MRSA and nasal colonisation with S. aureus is known to persist in a subset of individuals [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, S. aureus colonisation was associated with technology dependency. Other authors have reported higher rates of S. aureus colonization in tracheostomized children 30 , or in patients with percutaneous gastrostomy 31 In the same way, tracheostomy, nasoenteric or gastrostomy tube, or the use of intravenous devices have been reported as risk factors for MRSA acquisition 32 35 . Therefore, invasive devices might favor colonization via bacterial biofilm formation.…”
Section: Discussionmentioning
confidence: 93%
“…LA-MRSA infection and colonization is a serious condition that can occur in horses as well as in humans. The risk factors reported in cases of MRSA infection and colonization in humans were history of antibiotic administration, contact with hospital staff, history of previous hospitalization, and hospital overcrowding [57,[98][99][100][101]. Meanwhile, the reported risk factors for LA-MRSA infection and colonization in horses have not been adequately evaluated [102].…”
Section: Risk Factor For Spreading La-mrsa In Horsementioning
confidence: 99%